Constraining SIDM with halo shapes: Revisited predictions from realistic simulations of early-type galaxies - Despali, Giulia; Walls, Levi G; Vegetti, Simona; Sparre, Martin; Vogelsberger, Mark; Zavala, Jesús (Monthly notices of the Royal Astronomical Society, 2022)
We study the effect of self-interacting dark matter (SIDM) and baryons on the shape of early-type galaxies (ETGs) and their dark matter haloes, comparing them to the predictions of the cold dark matter (CDM) scenario.
Gesehen am 22.11.2022